Penerapan Model Pembelajaran Inkuiri Terbimbing untuk Meningkatkan Aktivitas dan Hasil Belajar IPA Fisika Siswa SMP - Karlina, Nini; Sahara, La; Sukariasih, Luh (Jurusan Pendidikan Fisika, 2019)
This study aims to : (1) describe the learning activities of students in learning science especially in the study of physics on the subject matter of light and optical devices in students of class VIII Togomangura Satap Junior High School taught through the guided inquiry learning model; (2) describing the improvement of science learning outcomes in the study of the physical subject matter of light and optical devices in grade VIII students of Togomangura Satap Junior High School which are taught through guided inquiry learning models; (3) describe the increase in completeness of natural science learning, especially in the physics study of eighth grade students of Togomangura Satap Junior High School who are taught by applying the guided inquiry learning model. The subjects of this study were all eighth grade students of Togomangura Public Middle School with 18 students, consisting of 11 men and 7 women. The data collection technique was carried out by observation and student learning achievement test in the form of a description test. Data analysis techniques using descriptiveÂ statistics. Based on the results of data analysis and discussion, it can be concluded that: (1) the learning activities of students by applying the guided inquiry learning model in each cycle tend to increase and improve in each unit of student activity. This is indicated by the acquisition of an average score of cycle I of 2,6 which belongs to the sufficient category and increased in cycle II to 3,8 which belongs to the good category; (2) science learning outcomes of students in class VIII Togomagura Satpap can be improved by applying the guided inquiry learning model to the subject matter of light and optical devices, where in cycle I is obtained an average value of 59,2 with a standard deviation of 22,9 and at cycle II obtained an average value of 65,6 with a standard deviation of 23,4; (3) completeness of science learning for students of class VIII Togomagura Satpap Junior High School taught through the use of guided inquiry learning models in each cycle tends to increase, where in cycle I the percentage of mastery learning outcomes is 27,8 % and in cycle II is 66,7 % .Â